2016
DOI: 10.18632/oncotarget.7301
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic acid inhibits 12-O-tetradecanoylphorbol-13- acetate-induced fascin-1-dependent breast cancer cell migration by suppressing the PKCδ- and Wnt-1/β-catenin-mediated pathways

Abstract: Fascin-1, an actin-bundling protein, plays an important role in cancer cell migration and invasion; however, the underlying mechanism remains unclear. On the basis of a 12-O-tetradecanoylphorbol 13-acetate (TPA)-induced cell migration model, it was shown that TPA increased fascin-1 mRNA and protein expression and fascin-1-dependent cell migration. TPA dose- and time-dependently increased PKCδ and STAT3α activation and GSK3β phosphorylation; up-regulated Wnt-1, β-catenin, and STAT3α expression; and increased th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 76 publications
1
36
0
Order By: Relevance
“…The expression of MMP‐9 and IL‐8 is directed by cis‐acting transcription regulatory elements for AP‐1 and NF‐κB transcription factors. In addition, STAT3 acts as a key transcription factor in the regulation of migration in breast cancer cells . We already showed that mLU8C‐PU decreases TPA‐induced mRNA and protein levels of MMP‐9 and IL‐8.…”
Section: Resultsmentioning
confidence: 92%
“…The expression of MMP‐9 and IL‐8 is directed by cis‐acting transcription regulatory elements for AP‐1 and NF‐κB transcription factors. In addition, STAT3 acts as a key transcription factor in the regulation of migration in breast cancer cells . We already showed that mLU8C‐PU decreases TPA‐induced mRNA and protein levels of MMP‐9 and IL‐8.…”
Section: Resultsmentioning
confidence: 92%
“…Angiogenesis is a vital step in the physiological process of tissue repair and regeneration, bone remodeling and reproduction, and embryonic development (Folkman, 2006;Garona et al, 2018;Annese et al, 2019). Moreover, it also played a critical role in the progression of tumor formation, infiltration, invasion, and metastasis (Carmeliet, 2006;Seano et al, 2014;Lii et al, 2016;Ao et al, 2017;Yang et al, 2017). Thus, inhibition of angiogenesis has become an effective strategy for cancer therapy.…”
Section: Tan Iia Inhibits Tumor Angiogenesismentioning
confidence: 99%
“…Commonly, TPA is employed as a tumor-promoting agent for skin carcinogenesis in rodents and is associated with increased cell proliferation in malignant cells from several types of tumors, such as melanoma and breast and oral cancer345. However, the function of TPA is controversial because a decrease in cell proliferation capacity has also been observed in TPA-treated lymphoma cells compared to controls67.…”
mentioning
confidence: 99%